1994
DOI: 10.1007/bf02012115
|View full text |Cite
|
Sign up to set email alerts
|

Sponastrime dysplasia: Report on a male patient

Abstract: We report on a boy in the fourth family known to be affected with sponastrime dysplasia. The clinical and radiological features are presented. In this patient, the ossification delay was severe. The pattern of inheritance of this condition is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

1996
1996
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 2 publications
2
15
0
1
Order By: Relevance
“…However, severe midface hypoplasia with saddle nose that presents as aǹ`o riental look'', micromelic short stature, and conspicuous modi®cation of the vertebral bodies in sponastrime dysplasia contrast with sloping forehead with beaked nose that presents as a``bird-headed pro®le'', almost proportional short stature, and normal appearance of the vertebral bodies in the present disorder, respectively. Two entities with super®cial radiological similarities to sponastrime dysplasia, including one entity reported by Camera et al [3] and Masuno et al [9], and the other by Camera et al [2] and Verloes et al [11], are also readily distinguishable from the present disorder.…”
Section: Discussionmentioning
confidence: 81%
“…However, severe midface hypoplasia with saddle nose that presents as aǹ`o riental look'', micromelic short stature, and conspicuous modi®cation of the vertebral bodies in sponastrime dysplasia contrast with sloping forehead with beaked nose that presents as a``bird-headed pro®le'', almost proportional short stature, and normal appearance of the vertebral bodies in the present disorder, respectively. Two entities with super®cial radiological similarities to sponastrime dysplasia, including one entity reported by Camera et al [3] and Masuno et al [9], and the other by Camera et al [2] and Verloes et al [11], are also readily distinguishable from the present disorder.…”
Section: Discussionmentioning
confidence: 81%
“…In our patient, this is not as pronounced as in the cases of Cooper et al 4 and Fanconi et al 6. The MCPP obtained by Camera et al 7 shows a much flatter pattern, further supporting the likelihood of a different condition in their patient. The pattern variability index (OZ) in this patient, based on the method described by Garn et al ,19 was calculated to be 0.51.…”
Section: Discussionmentioning
confidence: 56%
“…Since the first description of SEMDJL-l/H type by Hall et al [7] more than 20 cases have been reported. This implies that it might be a quite common skeletal dysplasia [7,8,10,12,[18][19][20][21][22][23]. The phenotypic and radiographic similarities among SEMDJL-l/H type, SEMDJL-B type and SD suggest that they might be pathogenetically related entities.…”
Section: Resultsmentioning
confidence: 98%